Strengthen the Role and Function of Bawaslu in Election Supervision and Law Enforcement - Hamimah, Siti (Law Research Review Quarterly, 2018)
In Law No.7 of 2017 the position of Bawaslu is strengthened by several changes to the rules. Some of these changes include increasing the number of Bawaslu members, expanding the authority of Bawaslu. Considering that 2018 and 2019 are election years and by looking at the history of Indonesian elections that are still a lot of violations, of course the new regulations on Bawaslu contained in Law No.7 of 2017 will affect the performance of Bawaslu in the future which is expected to be better compared to previous rules. The existence of Bawaslu in the process of conducting elections from time to time is increasingly considered important. Therefore, in any changes to the electoral law, changes regarding Bawaslu also occur. The change is nothing but to strengthen the existence of Bawaslu as an election supervisory institution. The strengthening of Bawaslu was seen at the time of the birth of Law No.15 of 2011 replacing Law No.22 of 2007. Important changes regarding the duties and authority of Bawaslu lie in the authority to resolve Election disputes which in Law No. 22 of 2007 was removed and returned to Bawaslu. In Article 259 of Law Number 8 of 2012, it is stipulated that the decision of the Election Supervisory Body in resolving election disputes is final and binding.